Successful secukinumab therapy in plaque psoriasis is associated with altered gut microbiota and related functional changes - Du, Xueshan; Yan, Cong; Kong, Shuzhen; Che, Delu; Peng, Bin; Zhu, Longfei; Geng, Songmei; Guo, Kun (Frontiers in Microbiology, 2023)
Introduction The role of gut microbiome dysbiosis in the pathogenesis of psoriasis has gained increasing attention in recent years. Secukinumab, targeting interleukin (IL)-17, has a promising efficacy in psoriasis treatment. However, it remains unclear the gut microbiota alteration and related functional changes caused by successful secukinumab therapy in psoriatic patients. Methods In our study, we compared the fecal microbiome profile between psoriatic patients after secukinumab successful treatment (AT) and the other two groups, psoriatic patients without therapy (BT) and healthy people (H), respectively, by using next-generation sequencing targeting 16S ribosomal RNA. Then, shotgun metagenomic sequencing was first used to characterize bacterial gut microbial communities and related functional changes in the AT group. Results We found that the diversity and structure of the microbial community in the AT group were significantly changed compared to those in the BT group and the H group. The AT group showed a microbiota profile characterized by increased proportions of the phylum Firmicute, families Ruminococcaceae, and a reduction in the phylum Bacteroidota (elevated F/B ratio). To detect functional alteration, we discovered that secukinumab treatment may construct a more stable homeostasis of the gut microbiome with functional alteration. There were different KEGG pathways, such as the downregulated cardiovascular diseases pathway and the upregulated infectious diseases in the AT group. By metagenomic analysis, the metabolic functional pathway was changed after secukinumab therapy. Discussion It seems that gut microbiota investigation during biologic drug treatment is useful for predicting the efficacy and risks of drug treatment in disease.